Mass spectrometric analysis of the kinetics of in vivo rhodopsin phosphorylation - Lee, Kimberly A. (Cold Spring Harbor Laboratory Press, 2002)
On stimulation, rhodopsin, the light-sensing protein in the rod cells of the retina, is phosphorylated at several sites on its C terminus as the first step in deactivation. We have developed a mass spectrometry–based method to quantify the kinetics of phosphorylation at each site in vivo. After exposing either a freshly dissected mouse retina or the eye of an anesthetized mouse to a flash of light, phosphorylation and dephosphorylation reactions are terminated by rapidly homogenizing the retina or enucleated eye in 8 M urea. The C-terminal peptide containing all known phosphorylation sites is cleaved from rhodopsin, partially purified by ultracentrifugation, and analyzed by liquid chromatography coupled with mass spectrometry (LCMS). The mass spectrometer responds linearly to the peptide from 10 fmole to 100 pmole. The relative sensitivity to peptides with zero to five phosphates was determined using purified phosphopeptide standards. High pressure liquid chromatography (HPLC) coupled with tandem mass spectrometry (LCMS/MS) was used to distinguish the three primary sites of phosphorylation, Ser 334, Ser 338, and Ser 343. Peptides monophosphorylated on Ser 334 were separable from those monophosphorylated on Ser 338 and Ser 343 by reversed-phase HPLC. Although peptides monophosphorylated at Ser 338 and Ser 343 normally coelute, the relative amounts of each species in the single peak could be determined by monitoring the ratio of specific daughter ions characteristic of each peptide. Doubly phosphorylated rhodopsin peptides with different sites of phosphorylation also were distinguished by LCMS/MS. The sensitivity of these methods was evaluated by using them to measure rhodopsin phosphorylation stimulated either by light flashes or by continuous illumination over a range of intensities.